A Trifluorinated Thiazoline Scaffold Leading to Pro‐apoptotic Agents Targeting Prohibitins1. Issue 38 (5th September 2014) - Pérez‐Perarnau, Alba; Preciado, Sara; Palmeri, Claudia Mariela; Moncunill‐Massaguer, Cristina; Iglesias‐Serret, Daniel; González‐Gironès, Diana M.; Miguel, Miriam; Karasawa, Satoki; Sakamoto, Satoshi; Cosialls, Ana M.; Rubio‐Patiño, Camila; Saura‐Esteller, José; et al.
Abstract A new class of small molecules, with an unprecedented trifluorothiazoline scaffold, were synthesized and their pro‐apoptotic activity was evaluated. With an EC50 in the low micromolar range, these compounds proved to be potent inducers of apoptosis in a broad spectrum of tumor cell lines, regardless of the functional status of p53. Fast structure–activity relationship studies allowed the preparation of the strongest apoptosis‐inducing candidate. Using a high performance affinity purification approach, we identified prohibitins 1 and 2, key proteins involved in the maintenance of cell viability, as the targets for these compounds.